2013
DOI: 10.1590/s1516-35982013000700001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on ponderal performance and morphometric characteristics of lambs of different genetic groups from birth to weaning

Abstract: -The objectives of this work were to evaluate the environmental effects (age of dam, type of birth and sex of lamb) and genetic groups (Hampshire Down and Ile de France, ½ and ¾ Hampshire Down, Ile de France and Suffolk, and ½ Texel) on performance and morphometric characteristics (height, length and heart girth) of lambs; to test regressions to predict live weight of lambs from body measurements; and to describe the growth type of the measurements as function of the weight. Weights and measurements were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
4
5
1
1
Order By: Relevance
“…These findings are closely similar to our results except for rump width. The chest circumference of Texel crosses was found to be 61.6 cm by Koritiaki et al (2013), and this value was lower than that of our study. The results of the current study showed that the longissimus muscle depth of BC 2 (+/−) lambs was higher than the Ramlıç and Texel lambs.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…These findings are closely similar to our results except for rump width. The chest circumference of Texel crosses was found to be 61.6 cm by Koritiaki et al (2013), and this value was lower than that of our study. The results of the current study showed that the longissimus muscle depth of BC 2 (+/−) lambs was higher than the Ramlıç and Texel lambs.…”
Section: Discussioncontrasting
confidence: 94%
“…A similar trend supporting our findings was observed by Han et al (2010) and Farhadian et al (2012). The birth weight (4.085 kg) of Texel lambs in the study was in the range of 3.70-5.00 kg reported for pure Texel and crosses (Estevá and Picard, 1989;Khusro et al, 2005;Koritiaki et al, 2013;Maxa et al, 2005;Wuliji et al, 1995). The birth weight of Texel lambs was significantly (P <0.05) lower than the other genotypes in the study.…”
Section: Discussionsupporting
confidence: 91%
“…The mean live weight obtained in the study was expressed as 43.6 kg. The chest circumference in weaning lambs carrying 50% Texel genotype was also 61.56 cm according to Koritiaki et al (23). Above mentioned growth characteristics were reported to be affected by different environmental factors such as sex, birth type, month of birth, year, and weaning age (15).…”
Section: Introductionmentioning
confidence: 96%
“…Research on the structure of the heart in different groups of animals includes, among others, the relationships between heart size and body size (Prothero, 1979;Heusner, 1991;Koritiaki et al, 2013), body performance and the effect of effort or its cessation on the morphological traits of the heart and cardiac contractility (Steel et al, 1976;Nielsen & Vibe-Petersen, 1980;Pape et al, 1984;Gunn, 1989), or the association of heart morphological parameters with various environmental factors (Viscor & Fuster, 1987;Simpson et al, 2007). In studies on the heart morphology, it is important to establish the relationship between the weight of this organ and the body weight, which may be induced by the level of growth and sex hormones being secreted or diet (Bailey et al, 2004;Simpson et al).…”
Section: Introductionmentioning
confidence: 99%